Influence of rice straw and wood fiber combination on physical and mechanical properties of rice straw pulverized composite board - Dhanapal, Sujatha; Singh, Mamatha; Nagammanavar, Uday (Maderas. Ciencia y Tecnología, 2024)
The production of particleboards from various kinds of ligno cellulosic materials are successful on commercial scale in various parts of the country. However, much success is not seen in use of crop residues for particleboards. Rice straw and wheat straw are one such materials that are abundantly available in India that can be used to produce particleboard. The present work investigated the effect of Rice straw particles and wood fibers combination on physical and mechanical properties of the composite board. The pulverized rice straw composite boards were produced with three different composition of rice straw material (100 %, 70 %, 50 %) and wood Fibers (0 %, 30 %, 50 %). Melamine Urea Formaldehyde (MUF), Phenol Cardanol Formaldehyde (PCF), Blocked Isocyanate resin combined with PCF (BPCF), Blocked Isocyanate combined with Urea Melamine Formaldehyde (BUMF) and Blocked Isocyanate combined with PF (BPF) resins were synthesized. The resin system (10%,12%,14%) with requisite additive was admixed with rice straw and wood fibers. According to the resin system employed, the hot press temperature, specific pressure and curing time were worked out for compression of the boards. The boards were produced with 780 - 850 kg/m3 nominal density and prior to testing, the test specimens were exposed to an atmosphere maintained at a relative humidity of 65 ± 5 percent and at a temperature of 27 ± 2 °C until their masses are nearly constant. The boards made were subjected for evaluation of physical and mechanical properties according to IS 3087. It was found that the Rice Straw particles with Wood Fibers of 50-50 combination bonded with PCF and also with MUF adhesive of 12 % resin solids confirms to the requirement of physical and mechanical properties as per IS 3087 particleboards of wood and other lignocellulosic materials (medium density) for general purposes Specification. Comparison with resin for hybrid boards of rice straw particles with wood fiber, BPCF has shown excellent properties than BPF and BUMF. The study indicated that increasing the percentage replacement of wood fibers with rice straw particles by more than 50 % decreased the internal bond strength. It can be concluded that rice straw pulverized particleboard can be successfully made with the combination of 30 % - 50 % wood fibers using PCF resin or BPCF resin.